Assessment of knowledge regarding issues related to adolescence among male students in Allahabad district, India - Anand, Deepak; Parveen, Khurshid; Prakash, Gyan (International Journal Of Community Medicine And Public Health, 2018)
Background: Providing information about changes during adolescence and sexually transmitted diseases is an important means of promoting healthy development and reducing negative outcomes of social behaviors in adolescents. For this purpose we must know their level of knowledge. So this study was designed to assess the knowledge of male students of class VIth to IXth about issues related to adolescence, their attitude for sexuality related problem and their source of information. Methods: It is a cross-sectional study, sample size was 400. Data was collected between August 2017 and December 2017 by using structured questionnaire. Results: Regarding physical changes 4.5% students have no knowledge, 58.75% have some knowledge and 36.75% have satisfactory knowledge. Whereas 9.75% have no knowledge, 80.75% have some knowledge and 9.50% have satisfactory knowledge regarding sexually transmitted diseases. Only 24.75% students knew legal age for marriage. Conclusions: It was found in study that majority of students do not have satisfactory knowledge and there is a need for targeted education for providing proper knowledge.